Entrepreneurial competencies and performance of Ugandan SMEs: the mediating role of firm capabilities - Moses Kisame Kisubi; Francis Aruo; Aziz Wakibi; Veronica Mukyala; Kassim Ssenyange (Cogent Business & Management, 2022)
The purpose of this study was twofold; (1) to establish the direct influence of Entrepreneurial competencies and Firm capability on SME Performance and (2) to examine the mediating role of Firm capability between Entrepreneurial competencies and SME Performance. A cross-sectional and explanatory design was utilized to collect and analyze data from 314 SMEs in Uganda. The sample size was proportionally distributed amongst three SME subsectors; manufacturing, trade, and restaurants. A positive and significant influence of entrepreneurial competencies and firm capabilities on SME performance was established. Among the seven entrepreneurial competencies understudy, innovative competency is highly associated with SME performance than other competencies. Interestingly, firm capabilities were found to be a powerful predictor of SME performance than entrepreneurial competencies. In addition, a partial and significant mediating role of firm capabilities was also found. Theoretically, the study provides maiden evidence of the indirect influence of a firm's capabilities on the association between entrepreneurial competencies and SME performance. In practice, managers and SME owners should address their competency deficiencies to develop more capabilities like management and marketing capabilities which could enhance SME performance. The study provides initial evidence for the mediating role of firm capabilities in the association between entrepreneurial competencies and firm performance.
Keywords: 650; SMEs; Uganda; firm performance; entrepreneurship; entrepreneurial competencies; firm capabilities